Heritage Regeneration, Planning, and Resistance: The Bell and Drum Towers Area in Beijing - Tam, Lui (International Planning History Society Proceedings, 2024)
This paper examines the evolution of urban heritage regeneration approaches in the Bell and Drum Towers (BDT) area in the past one and a half decades. At the heart of Beijing’s historic centre and the north end of its historic Central Axis, the BDT area is one of the most iconic landmarks of the metropolis. The BDT area comprises some of the historic city centre’s most intact and lively neighbourhoods. However, it has had its share of controversies, particularly during the regeneration project from 2010-2014. The square between the two towers and surrounding neighbourhoods became a stage of political tension, urban activism, and grassroots resistance, which were then ‘wiped clean’ nearly overnight. Although the noises have faded in the last decade, more subtle changes have picked up pace in preparation for the 2024 World Heritage inscription application of Beijing’s Central Axis. Through critically examining the planning framework governing the BDT area’s heritage management, the projects and controversies over the past 15 years, this paper highlights how heritage has been used in the somewhat fluid narratives for urban heritage regeneration in Beijing. It argues that some of these issues are emblematic of the low-rise and high-density historic urban areas with high land value, which remain sources of tension in the metropolis.